On the epistemic role of moral disgust in fiction: What can we learn from affective or empathetic engagement with vicious perspectives - Kyprianidou, Efi (My University, 2025)
One of the most interesting aspects of our engagement with fiction is that we often enjoy imaginatively engaging with morally flawed narratives or vicious perspectives. Yet, it sometimes happens that our ability to imaginatively engage with certain kinds of vicious perspectives is reduced or even suspended. In this paper, I will consider a particular aspect of resistance, namely, resistance to emotional or empathetic engagement with fiction (affective puzzle). To do so, I will examine a specific shortcoming within the current discourse. In addressing the relative difficulties in engaging with vicious perspectives, existing accounts of imaginative resistance acknowledge that readers may experience disgust or aversion, but they do not differentiate between distinct types of moral-related disgust or trace how each type influences our engagement with fiction. As the role of disgust in morality is debated and there are contrasting accounts of the nature of moral-related disgust, I argue that to fully explore the phenomenon, we must distinguish between two different types of moral-related disgust, each influencing our imagination in distinct ways. On the one hand, physical disgust that inscribes within the realm of morality by being causally linked to moral disapprobation, and, on the other hand, genuine moral disgust, that is a response to the morally reprehensible and is itself a moral emotion. I will describe the differences between these emotions and explain how they interact with implicit beliefs, biases, and attitudes - such as desires- prompting us to control our affective engagement with a vicious perspective. Ultimately, this finer-grained account illuminates the epistemic role of moral disgust: it shows how the limitations in our engagement with vicious perspectives are sometimes an indication of biased ways of seeing the world, while other times, they are a sign of moral character.